Groundwater quality in coastal area: A case study in Parangtritis Village, Bantul, Yogyakarta, Indonesia - Septian Putri Antika; Sadewa Purba Sejati; Mohd Hairy Ibrahim (Universitas Negeri Malang, 2024)
Groundwater in coastal areas is one of the natural resources that is vulnerable to quality degradation due to population activities in coastal areas. This is also the case in Parangtritis Village, a coastal area with various potential regions for the population's welfare, ranging from tourism to agriculture, animal husbandry, and fisheries. Therefore, this study explores groundwater quality in Parangtritis Village, Kretek District, Bantul Regency, Yogyakarta. Groundwater quality data was collected through field surveys based on land use, with water quality parameters including odor, color, nitrate, nitrite, and E. coli. The Minister of Health Regulation Document Number 32 of 2017 was adopted as a benchmark for groundwater quality in the research area. Further, by using the gathered data, the groundwater quality was classified based on limiting parameters. Groundwater quality is distributed based on limiting parameters such as odor, color, nitrite, and E. coli bacteria. Odor and color limitations are found in agricultural areas, tourism areas, and fish farms. Nitrite limitations are found in residential and livestock areas. E. coli bacteria limitations are found in all land use areas.